Pregnancy In An Untreated Case of Tranverse Vaginal Septum with Urethrovaginal Fistula: A Case Report and Review of the Literature - Nawaz, Rafat (Bangladesh Journal of Obstetrics & Gynaecology, 2011)
A 17 years old married woman presented at 24 weeks pregnancy with absent foetal movement for 12 days. She was found to have transverse vaginal septum in the lower third of her vagina with urethro-vaginal fistula (UVF) and a dead foetus of approximately 24 weeks gestation. She underwent hysterotomy for the delivery of the dead foetus. Two and half months later the transverse vaginal septum was removed with repair of urethro-vaginal fistula. Bangladesh J Obstet Gynaecol, 2009; Vol. 24(2) : 71-74 DOI: http://dx.doi.org/10.3329/bjog.v24i2.8532